1994
DOI: 10.1152/ajpgi.1994.266.6.g1146
|View full text |Cite
|
Sign up to set email alerts
|

Direct in vivo adenovirus-mediated gene transfer to salivary glands

Abstract: Gene transfer to the salivary glands holds the potential for the therapy of salivary gland disorders and for delivery of therapeutic proteins to the mouth and upper gastrointestinal tract. Administration of the recombinant adenovirus vectors Ad.RSV beta gal [coding for the intracellular protein beta-galactosidase (beta-Gal)] and Ad alpha 1AT [coding for human alpha 1-antitrypsin (alpha 1-AT), a secreted protein] to salivary gland cell lines in vitro demonstrated exogenous gene expression. Retrograde ductal inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0
2

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 0 publications
4
107
0
2
Order By: Relevance
“…10,16 Those studies have suggested several potentially useful clinical applications of this maneuver. Preclinical studies examining adenoviral-mediated gene transfer to the salivary glands of non-human primates should provide valuable information for eventual, planned human studies, based on the results of several studies using recombinant adenoviruses encoding the cystic fibrosis transmembrane conductance regulator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,16 Those studies have suggested several potentially useful clinical applications of this maneuver. Preclinical studies examining adenoviral-mediated gene transfer to the salivary glands of non-human primates should provide valuable information for eventual, planned human studies, based on the results of several studies using recombinant adenoviruses encoding the cystic fibrosis transmembrane conductance regulator.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Figure 5A demonstrates positive immunostaining for AQP1, primarily in capillaries and venules in control gland tissue (AdCMVH3; animal E). In animals receiving AdhAQP1, positive staining was seen in some acinar and ductal elements in addition to the vascular immunoreactivity.…”
Section: Expression Of Haqp1 In Salivary Parenchymal Cellsmentioning
confidence: 99%
“…10,13 Each rat received 5 × 10 9 p.f.u. of AdCMVhGH in 50 l aliquots either by intramuscular injection (quadriceps), intravenous infusion (tail vein or femoral vein; with similar results) or by submandibular duct cannulation.…”
Section: In Vivo Gene Transfermentioning
confidence: 99%
“…Salivary glands provide an extremely convenient target tissue for in vivo gene transfer. 13 These glands are readily accessible through the oral cavity, via their excretory ducts, without the need for surgical manipulations. Virtually all parenchymal cells in the gland line the ductal system and are potential targets for in vivo gene transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation